(untitled) (Agro Productividad, 2022)
Objective: To analyze the occurrence of the reproductive seasonality and its relation to the time of the year, feeding, race, and social environment of sheep in the municipality of Singuilucan, Hidalgo, Mexico. Design/methodology/approach: Forty-one surveys with sheep breeders were carried out. The data obtained was subject to a logistic regression analysis, in order to analyze the degree to which the said variables intervene on the occurrence or absence of seasonal anestrus periods in ewes. The environment in which they are developed and the traditional handling of production units must be taken into account. Results: Seasonal anestrus periods have been recorded in 95.1% of the production units; such variables as seasons of the year, feeding type, race, and social environment have a significant influence (P<0.05). Spring is the most influential season of the year with regard to the occurrence of anestrus periods (P<0.05). The reproductive season reaches its peak in late spring and in summer; ewes give birth in late autumn and in winter. Study limitations/implications: Reproductive seasonality limits sheep production systems. Findings/conclusions: Estrus take place in late spring and early summer. The season of the year, feeding type, race, and social environment are variables that influence the occurrence of seasonal anestrus in spring.